2021
DOI: 10.1007/s13258-021-01160-6
|View full text |Cite
|
Sign up to set email alerts
|

MiR-200c-3p aggravates gastric cell carcinoma via KLF6

Abstract: Background Gastric cell carcinoma (GCC) is a common and high-incidence malignant gastrointestinal cancer that seriously threatens human life and safety. Evidences suggest that microRNAs (miRNAs) exhibit an essential role in regulating the occurrence and development of GCC, while the effects and possible mechanisms remain to be further explored. Objective This study was designed to explore whether miR-200c-3p exerted its functional role in the growth and me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…It was found that miRNA 200-c-3p can act as a positive or negative regulator of epithelial-mesenchymal transition (EMT) in different cells and tissue types [20][21][22]. MiRNA 200-c-3p can modulate tumor proliferation, invasion and metastasis by acting differentially on the EMT process [23][24][25]. Due to its differential expression and actions in various tissue and cells, miRNA 200-c-3p is reported as being either a tumor-suppressive or an oncogenic miRNA in many cancer types [24,25].…”
Section: Original Articlementioning
confidence: 99%
“…It was found that miRNA 200-c-3p can act as a positive or negative regulator of epithelial-mesenchymal transition (EMT) in different cells and tissue types [20][21][22]. MiRNA 200-c-3p can modulate tumor proliferation, invasion and metastasis by acting differentially on the EMT process [23][24][25]. Due to its differential expression and actions in various tissue and cells, miRNA 200-c-3p is reported as being either a tumor-suppressive or an oncogenic miRNA in many cancer types [24,25].…”
Section: Original Articlementioning
confidence: 99%
“…After the discovery of miRNAs and by advances in field of biology and next generation sequencing, miRNA's role in diseases and cancer was evaluated (Zhang et al 2021b; Li et al 2021c; Tanaka et al 2021; Xie et al 2021). It has been shown that miRNA‐200c‐3p increases growth and invasion of gastric tumor by KLF6 suppression (Wang et al 2021a). miRNA‐199b‐5p‐induced EMT enhances metastasis by HHIP inhibition (Chen et al 2021a).…”
Section: Mirnas: Biogenesis and Carcinogenesis Regulationmentioning
confidence: 99%
“…We found that compared to other clusters, cluster 1 and cluster 4 had higher expression of KLF6, PRDM1, STAT1, JUNB, and HES1 (Figure 3I). Researchers have reported that KLF6 plays an essential role in immunosuppression and modulates neutrophil maturation (38)(39)(40)(41)(42), while PRDM1 is a crucial epigenetic gene associated with T-cell terminal differentiation (43,44). In other words, targeting PRDM1 would enable the generation of superior antitumor T cells.…”
Section: Macrophages Are Related To the Immunosuppressive Environment...mentioning
confidence: 99%